2001
DOI: 10.1590/s0102-311x2001000300013
|View full text |Cite
|
Sign up to set email alerts
|

Taxa de adequação (ingestão/requerimento) de energia como indicador do estado nutricional das famílias: uma análise crítica dos métodos aplicados em pesquisas de consumo de alimentos

Abstract: The authors discuss problems associated with the use of the energy adequacy ratio as an indicator of nutritional status in population-based studies derived from household food consumption surveys. They describe the use of food consumption data to estimate family energy intake and to compare it among families and with family requirements to determine the family energy adequacy ratio. The article also discusses the use of international recommendations for human energy requirements and their limitations, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
5
0
4
Order By: Relevance
“…Thus, the main differences between these scales relates to the individual used as the reference (reference adult) and the choice of the set of calorie requirements 8,9,10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the main differences between these scales relates to the individual used as the reference (reference adult) and the choice of the set of calorie requirements 8,9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors also observed that the per capita values tended to underestimate the real calorie availability. Use of the adultequivalent scale also reduced the variability in household calorie intake, proving to be the most precise method for estimating calorie consumption using household budget surveys 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dentre as alternativas de valor de MC destacam-se: • a MC observada; • a MC de referência; • a MC saudável 15 . Vasconcellos e Anjos 16 indicam que o uso dos valores da MC observada é adequado aos estudos de seguridade e abastecimento alimentar de uma população, quando o objetivo é a determinação da demanda de energia proveniente dos alimentos. Os valores de referência são usados quando o objetivo é determinar requerimentos que assegurem, a todos, tamanho e composição corporais compatíveis com a boa saúde a longo prazo e um nível de atividade física socialmente desejável e economicamente necessário.…”
Section: As Recomendações Internacionais De 1985unclassified